Peningkatan Motivasi Belajar Siswa melalui Media Interaktif pada Mata Pelajaran SKI di SD - Asyraf, M.; Andary, Lisa; Sastrawati, Eka; Nazurti, Nazurti; Indryani, Indryani (MODELING: Jurnal Program Studi PGMI, 2024)
This research discusses interactive media in increasing the learning motivation of fourth grade students in the History of Islamic Culture subject in elementary schools. In the beginning, fourth grade elementary school students did not have enthusiasm for learning and also with the rapid development of technology today, we need to utilize this technology in the field of education. This research focuses on increasing the learning motivation of fourth grade students in elementary schools. And this research uses the classroom action research method. The data collection stage went through several stages, namely, interviews, lesson plans, questionnaires, motivation and documentation. Classroom action research must also be carried out for a minimum of 2 cycles. After carrying out cycle I and cycle II learning activities using interactive media, the motivation and even enthusiasm of class IV students experienced a significant increase in learning, so that we can draw the conclusion that by using interactive media we can increase students' learning motivation in the Cultural History subject. Islamic class IV elementary school.